Curcumin and piperine loaded zein-chitosan nanoparticles: Development and in-vitro characterisation - Yücel Baspinar; Mehmet Üstündas; Oguz Bayraktar; Canfeza Sezgin (Elsevier, 2018)
Curcumin as the active compound of turmeric has antioxidative, antiinflammatory, antimicrobial and anticancer properties among others. However, its disadvantageous properties like low solubility, poor bioavailability and rapid degradation under neutral or alkaline pH conditions or when exposed to light limit its clinical application. These problems can be solved by a smart combination of using a natural enhancer like piperine and preparing nanoparticles by a proper method like electrospray.Due to these facts it was aimed in this study to develop curcumin and piperine loaded zein-chitosan nanoparticles step by step. For that purpose various formulation parameters like the concentrations of zein, curcumin, piperine and chitosan and the preparation parameters like the applied voltage and the nozzle diameter were investigated step by step. The nanoparticles were characterised by investigating their shapes, morphologies, particle sizes with help of SEM images and the cytotoxicity on neuroblastoma cells.It was succeeded to prepare curcumin and piperine loaded zein-chitosan nanoparticles having a mean particle size of approximately 500 nm and high encapsulation efficencies for curcumin (89%) and piperine (87%). Using a curcumin concentration of 10-25 µg/ml resulted in reduction of the viability of approximately 50% of the neuroblastoma cells. The here developed nanoparticle formulation consisting of solely natural compounds showed good cytotoxic effects and is a promising approach with appropriate properties for final consumption.